Air quality from a social perspective in four European metropolitan areas: Research hypothesis and evidence from the SEFIRA project. Issue 65 (November 2016) - Giardullo, Paolo; Sergi, Vittorio; Carton, Wim; Kenis, Anneleen; Kesteloot, Chris; Kazepov, Yuri; Kobus, Dominik; Maione, Michela; Skotak, Krzysztof; Fuzzi, Sandro; Pollini, Francesca
Highlights: Air quality policy analysis applying a cross-national comparative research design. From intervention analysis to the understanding of the implementation strategies. This approach disentangled the complexity behind the implemented choices. This integrated strategy is encouraged for implementing of new air quality policy. Abstract: This paper analyses social constraints influencing air quality governance in four European Union (EU) countries. The comparative analysis carried out here is the outcome of the EU FP7 SEFIRA project. Starting from study of implemented measures the paper marks out the structure of double-delegation in policy-making for air quality governance; that is to say the delegation from the EU to national governments who further delegate to regional and local authorities the burden to put in place concrete measures. Therefore, our analysis has followed a multi-level approach considering all the territorial level down to the urban scale. In doing so, we found out commonalities in the strategies which have been followed by policy-makers. The comparison has been made possible through the analysis of operationalised categories such as Domain, Objectives and Modalities on air quality plans. The analysis went further: through interviews with selected key stakeholder the social constraints which may limit the choices made by institutions have been investigated. The -lack of- success in attaining EU requirements for the air quality cannot be considered only as the outcome of the −lack of- awareness of which may be the best practices or choices, rather as the result of complex entanglements of social forces. Indeed, one of the main outcomes of this explorative investigation has been the breakdown of such complexity into its social component in a comparative study. The paper finally points out the need to promote an integrated approach for air quality policy as a strategy for the design of new measures for the future.